Mineralogy, fluid inclusions and C–H–O–S–Pb isotopes of the Palaeocene Longgen Pb-Zn deposit in the western Nyainqentanglha belt, Tibet - Zhang, Yong-chao; Gao, Shun-bao; Zheng, You-ye; Jiang, Jun-sheng; Zhang, Shu-zhi; Jiang, Xiao-jia; Guo, Xin-ran (Ore geology reviews, 2018)
[Display omitted] •With the granite porphyry intrusions as the center outward form alteration zonation.•From stage I to stage V, ore-forming fluids gradually evolved from magmatic to meteoric water in origin.•Ore-forming materials were derived mainly from the granite porphyry.•The Longgen Pb–Zn deposit is a typical skarn deposit.•Fluid cooling caused by fluid mixing was the most crucial mechanism for Pb-Zn deposition. The medium-sized Longgen Pb-Zn deposit deposit (proven Pb + Zn resources of 0.13 Mt, 3.21% Pb and 2.43% Zn) is located in the western Nyainqentanglha belt in southern Tibet. The orebodies occurring as stratiform, lenticular and vein types are hosted in the skarn or marble along the contacts between the limestones and the granite porphyries. Alteration zonations are observed from granite porphyry to limestone, the proximal garnet is reddish-brown and becomes more pale brown and green with distance. The values of grossular gradually increase, while the andradite end members gradually decrease with distance (And(92.5−99.5)Gro(0.5−7.5)Pra(0.0−0.1) to And(9.0−36.5)Gro(63.4−90.9)Pra(0.1−0.5)). Similarly, the values of diopside (Di9.2–30.4Hd65.9–89.9 Jo0.6−3.7 to Di65.2–77.6Hd21–33.2Jo1.3−1.7) gradually increased close to the limestone. Retrograde metasomatic minerals overprint the prograde skarn and are dominantly composed of epidote, actinolite, ilvaite, and chlorite. The ore minerals consist mainly of galena and sphalerite, followed by magnetite, pyrite, pyrrhotite, chalcopyrite, molybdenite and bornite. At least five stages have been recognized, and from stage I to stage V, the δ18Ofluids values are 7.7% to 8.3%, −6.0% to −4.4%, −8.8% to −6.4%, −8.7% to −3.3%, and −13.2%, respectively. The δD values from stages I to V are −141.1% to −129.4%, −136.5% to −124.2%, −129.5% to −106.4%, −126.6% to −101.4%, and −106.8%, respectively. The δD and δ18Ofluids indicate that the ore-forming fluids gradually evolved from magmatic to meteoric in origin. The main types of fluid inclusions for the Longgen deposit are liquid-rich inclusions. Laser Raman analysis indicates that the fluid inclusions within the studied minerals are dominated by H2O, although some contain CO2 gas. Given the fluid inclusion data, the ore-forming fluids of stages I and II were most likely high-temperature (460–480 and 340–360 °C) and low-moderate salinity (7.9–15.0 and 2.4–12.6 wt% NaCl eq.) fluids, which were formed in a magmatic–hydrothermal system in stage I and as a mixture of magmatic and meteoric waters in stage II. In the subsequent stages (III and IV), the fluids changed to moderate temperature (230–270 and 160–200 °C) and low-moderate salinity (0.2–14.8 and 0.9–10.6 wt% NaCl eq.) mixed fluids of magmatic and meteoric waters. In the last stage V, the fluids changed to low-temperature (130–160 °C) and low-salinity (0.2–5.6 wt% NaCl eq.) meteoric water. The δ13C values in calcite lie within a narrow range of −6.1% to −4.4%, similar to that for the magmatic source, which indicates that the carbon was sourced from the granite porphyry. Sulfur (δ34S = 0.4–5%, estimated δ34Sfluids = 2.77%) and lead isotopic compositions of sulfides (206Pb/204Pb = 18.549–18.776, 207Pb/204Pb = 15.685–15.839 and 208Pb/204Pb = 38.94–39.592, similar to the whole-rock values for the granite porphyry) indicate that the ore-forming materials were derived mainly from the granite porphyry, which originated from the Nyainqentanglha Group. Consequently, taking the data together suggests that the Longgen Pb–Zn deposit is a typical skarn deposit related to Palaeocene magmatic-hydrothermal systems, and that fluid cooling caused by fluid mixing is the most crucial mechanism for Pb-Zn deposition.